Social Development or Economic Development: The Dilemma Behind an Ambitious Infrastructure Development - Hasidin, Mirza Hapsari; Nugrahanti, Trinandari Prasetyo; Huda, Imam Walid Asrofuddin Ulil; Bajuri, Ahmad; Helmayuni, Helmayuni (International Journal of Demos (IJD), 2022)
Abstract The construction of the One Belt One Road (OBOR) infrastructure is a reasonably ambitious development. However, at the same time, there are several dilemmas faced by the Indonesian government. This research will examine the potential and obstacles to the ambitious OBOR infrastructure development in Indonesia. This research will be carried out using a qualitative approach. The data used in this study comes from previous research and studies that still have the same discussion as this research. This study found that OBOR infrastructure development can potentially increase the connectivity of waters in Indonesian territory. This will lead to an even social and economic development distribution throughout Indonesia. However, at the same time, several dilemmas need to be faced by the Indonesian government in building OBOR infrastructure. Keywords: One Belt One Road (OBOR), Development, Infrastructure. Abstrak Pembangunan infrastruktur One Belt One Road (OBOR) merupakan pembangunan yang cukup ambisius. Namun, pada saat yang sama, ada beberapa dilema yang dihadapi pemerintah Indonesia. Riset ini akan mengkaji potensi dan hambatan pembangunan infrastruktur OBOR yang ambisius di Indonesia. Penelitian ini akan dilakukan dengan menggunakan pendekatan kualitatif. Data yang digunakan dalam penelitian ini berasal dari penelitian sebelumnya dan penelitian yang masih memiliki pembahasan yang sama dengan penelitian ini. Kajian ini menemukan bahwa pembangunan infrastruktur OBOR berpotensi meningkatkan konektivitas perairan di wilayah Indonesia. Hal ini akan mengarah pada pemerataan pembangunan sosial dan ekonomi di seluruh Indonesia. Namun, pada saat yang sama, beberapa dilema perlu dihadapi pemerintah Indonesia dalam membangun infrastruktur OBOR. Kata kunci: One Belt One Road (OBOR), Pembangunan, Infrastruktur.